Idiopathic Acquired Hemophilia A with Undetectable Factor VIII Inhibitor - Nicholas B. Abt; Michael B. Streiff; Christian B. Gocke; Thomas S. Kickler; Sophie M. Lanzkron (Case Reports in Hematology)
Objective. We present the case of a 73-year-old female, with no family or personal history of a bleeding disorder, who had a classic presentation for acquired hemophilia A. Factor VIII activity was low but detectable and a factor VIII inhibitor was undetectable. Methods. The patient’s plasma was comprehensively studied to determine the cause of the acquired coagulopathy. Using the Nijmegen modification of the Bethesda assay, no factor VIII autoantibody was measureable despite varying the incubation time from 1 to 3 hours. Results. The aPTT was prolonged at 46.8 seconds, which did not correct in the 4 : 1 mix but did with 1 : 1 mix. Using a one stage factor VIII activity assay, the FVIII activity was 16% and chromogenic FVIII activity was also 16%. The patient was treated with recombinant FVII and transfusion, significantly reducing bleeding. Long-term therapy was initiated with cyclophosphamide and prednisone with normalization of FVIII activity. Conclusions. Physicians can be presented with the challenging clinical picture of an acquired factor VIII inhibitor without a detectable inhibitor by the Bethesda assay. Standard therapy for an acquired hemophilia A should be considered.